The chain mediating role of family health and physical activity in the relationship between life satisfaction and health-promoting lifestyles among young adults in China - Liu, ZhaoZhi; Huang, Li; Tian, HaoDong; Liu, HaoWei; Luo, HaoYue; Tao, YunFei; Peng, Li (Frontiers in Public Health, 2024)
Background: Unhealthy lifestyles during adolescence are significant factors leading to chronic diseases in the future. Enhancing health-promoting lifestyles among young adults in China is crucial for preventing and reducing the risk factors of chronic diseases.Objective: This study aims to explore the relationships between life satisfaction, family health, physical activity, and health-promoting lifestyles among young adults in China. It also seeks to confirm the chain mediation role of family health and physical activity in the influence of life satisfaction on health-promoting lifestyles in this population. Methods: This study, conducted from August 2023 to November 2023, employed a random sampling method to recruit young adult participants aged 18 to 40 in the southwestern region of China. Variables were measured using the Satisfaction with Life Scale (SWLS), the Family Health Scale-Short Form (FHS-SF), the Physical Activity Rating Scale-3 (PARS-3), and the Health-Promoting Lifestyle Profile II Revised (HPLP-IIR). Data analysis was performed using SPSS 27.0 and the PROCESS macro version 4.1. Results: The results indicated that life satisfaction was positively correlated with family health (r = 0.225), physical activity (r = 0.245), and health-promoting lifestyles (r = 0.506). Family health was positively correlated with physical activity (r = 0.320) and health-promoting lifestyles (r = 0.312). Physical activity was positively correlated with health-promoting lifestyles (r = 0.429). Additionally, life satisfaction could influence health-promoting lifestyles directly (effect = 0.369) and through three mediation pathways: (a) family health (effect = 0.033); (b) physical activity (effect = 0.050); (c) family health and physical activity (effect = 0.020).This study supports the mediating role of family health and physical activity in the influence of life satisfaction on health behaviors among young adults in China. Therefore, we recommend that future public health initiatives place greater emphasis on family health and create conditions that facilitate physical activity for this group. This could be an important direction for further enhancing health-promoting lifestyles among young adults in China.